2022
DOI: 10.3389/fphy.2022.887171
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review of Calibration-Free Laser-Induced Breakdown Spectroscopy

Abstract: The calibration-free laser-induced breakdown spectroscopy (CF-LIBS) technique requires no reference samples of the same matrix to establish the calibration curve, not affected by the matrix effect. In recent years, the CF-LIBS technology has greatly progressed, and the accuracy of quantitative analysis has gradually improved. The purpose of this review was to introduce the CF-LIBS fundamental and modified algorithms. The Boltzmann plot method, Saha–Boltzmann plot method, and column density Saha–Boltzmann plot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Reviews that cover detailed applications can be found elsewhere; for instance: Zhang et al 114 reviewed the recent advances in the use of LIBS for in situ and online detection of pollutants under atmospheric environments; Liu et al 115 reviewed novel approaches of LIBS for coal analysis; Khan et al 116 discussed the pros and cons of different LIBS methods to improve the detection of trace elements; and Marina-Montes et al 117 described a new protocol for particulate matter characterisation in filters using LIBS. Hu et al , 118 Wang et al 119 and Zhang et al 120 described advances in LIBS quantification methods, in particular related to calibration-free LIBS methods (CF-LIBS), which allows quantitative analysis without the use of standards. In these studies, the authors included a description of the basic theory, novel modifications/variations of the quantification methods, applications in a variety of fields and a discussion about the existing drawbacks.…”
Section: Laser-based Atomic Spectrometrymentioning
confidence: 99%
“…Reviews that cover detailed applications can be found elsewhere; for instance: Zhang et al 114 reviewed the recent advances in the use of LIBS for in situ and online detection of pollutants under atmospheric environments; Liu et al 115 reviewed novel approaches of LIBS for coal analysis; Khan et al 116 discussed the pros and cons of different LIBS methods to improve the detection of trace elements; and Marina-Montes et al 117 described a new protocol for particulate matter characterisation in filters using LIBS. Hu et al , 118 Wang et al 119 and Zhang et al 120 described advances in LIBS quantification methods, in particular related to calibration-free LIBS methods (CF-LIBS), which allows quantitative analysis without the use of standards. In these studies, the authors included a description of the basic theory, novel modifications/variations of the quantification methods, applications in a variety of fields and a discussion about the existing drawbacks.…”
Section: Laser-based Atomic Spectrometrymentioning
confidence: 99%
“…To mitigate these problems, several adaptations of CF-LIBS have been proposed [103]. Recent review publications [104,105] provide a detailed discussion of foundational concepts, their influencing factors, analytical efficacy, and potential measurement uncertainties.…”
Section: Classic and Calibration-free Libsmentioning
confidence: 99%
“…Calibration-free methods are a class of analytical methods that do not require any reference samples and are matrix independent. 38 Boric acid with natural 11 B and 10 B isotopes is chosen for the authentication of this technique. An algorithm was developed based on Born-Oppenheimer approximation, Boltzmann Equilibrium, and the Lorentzian intensity prole using the Levenberg-Marquardt method of non-linear curve tting for the analysis of experimental molecular spectra with theoretical simulated molecular spectra of the BO molecule.…”
Section: Introductionmentioning
confidence: 99%